Exploring intentions: factors influencing international study decisions in healthcare bachelor degree programs - Ann Kristin Bjørnnes; Astrid Torbjørnsen; Björg Sigridur Anna Thordardottir; Anne Lund; Olav Johannes Hovland; Lisebet Skeie Skarpaas (BMC Medical Education)
Abstract Background Study abroad programs offer significant benefits for healthcare students, including enhanced cultural awareness and professional development. However, participation in these programs is often influenced by various enablers and barriers. Understanding students’ characteristics, preferences, and knowledge about exchange opportunities is important for supporting students and developing strategies to facilitate exchange. Methods This study conducted a cross-sectional survey among students enrolled in four 3-year professional health bachelor’s programs in Norway. It aimed to investigate students’ characteristics, preferences, and knowledge about exchange opportunities. Additionally, it sought to examine enablers and barriers to exchange, as well as associations between students’ characteristics and their intention to participate in exchange programs. Results The survey results (N = 192) suggest associations between social relationships, financial considerations, personal motivations, and students’ decisions regarding participation in exchange programs. Conclusion This study provides a more nuanced understanding of students’ characteristics, preferences, and barriers associated with the intention to participate in international exchange opportunities within health science programs. Institutions should address the practical and personal challenges that students may encounter, thereby ensuring equitable access and participation. Furthermore, the study offers insights into the initial stages of the exchange process, focusing not only on those who choose to participate in exchange programs but also on those who opt out.